Host dependent electrocatalytic hydrogen evolution of Ni/TiO2 composites. Issue 10 (11th February 2021) - Zhou, Peng; Wang, Shuhua; Zhai, Guangyao; Lv, Xingshuai; Liu, Yuanyuan; Wang, Zeyan; Wang, Peng; Zheng, Zhaoke; Cheng, Hefeng; Dai, Ying; Huang, Baibiao
Abstract : The result shows that there is a stronger interaction between Ni and TiO2 when Ni is the host material compared with that with TiO2 as the host material. And the former displays a more obvious promotion effect on the HER performance. Abstract : Ni/TiO2 as a classic system has been widely studied in the traditional catalysis field including the water-gas shift reaction and selective oxidation/hydrogenation. However, in terms of the electrocatalytic hydrogen evolution reaction (HER), there is still a lack of systematic research on the actual synergistic promotion effect on the performance, and the influence of the host material on the electronic interaction between Ni and TiO2 is still unclear. Herein, we synthesized a series of Ni/TiO2 composites with different forms and tested the relevant HER performance. The results show that Ni/TiO2 exhibits much better HER performance than pure Ni and there is one type of electronic interaction between Ni and TiO2 in the composite with different forms, that is, electrons transfer from Ni to TiO2 . However, the interaction strength is host dependent, and the composite with Ni as the host displays the strongest interaction, and therefore the best HER performance (46 mV at 10 mA cm −2 ).